(3JaSjQ GdbQBfs - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdnqSnerQnbrfOj, CHh GddjK, GdedbH HEeGe GdgOi,J (B373 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf EdG Ydi GdXGdejf hGdUdGI hGdSdGe Ydi eMeO SjO GdeQSdjf hYJQJg GdWGgQjf HGH GdMK Ydi WdH JaSjQ GdbQBf s
(3BNQgG (B:s
(3Je GdeLdO GdChd ef JaSjQ CHj GddjK GdSeQbfOi HMeO Gddg hMSf Jhajbgq s
(3GdfSNI HgG MhGTs
(3Ydi dhMI GdYfhGf Jedcs
(3ai Chd GdfSNI agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs